Dissolution enhancement of glimepiride using modified gum karaya as a carrier - Nagpal, Manju; Rajera, Rampal; Nagpal, Kalpana; Rakha, Pankaj; Singh, SK; Mishra, DN (International Journal of Pharmaceutical Investigation)
Objective: The aim of present investigation is to enhance in vitro dissolution of poorly soluble drug glimepiride by preparing solid dispersions using modified gum karaya. Materials and Methods: Solid dispersions of drug were prepared by solvent evaporation method using modified gum karaya as carrier. Four batches of solid dispersion (SD1, SD4, SD9, and SD14) and physical mixture (PM1, PM4, PM9, and PM14) were prepared and characterized by differential scanning colorimetry (DSC), Fourier transform infrared (FTIR) spectroscopy, powder X-Ray diffraction (X-RD), and scanning electron microscopy (SEM) studies. Equilibrium solubility studies were carried out in shaker incubator for 24 h and in vitro drug release was determined using USP Dissolution Apparatus-II. Results: Maximum solubility and in vitro dissolution were observed with Batch SD4. No significant enhancement of dissolution characteristics were observed in the corresponding physical mixture PM4. Low viscosity with comparable swelling characteristics as compared to GK of modified form of gum karaya may lead to improvement in dissolution behavior of solid dispersion batches. Also, the conversion of crystalline form of drug to amorphous form may be a responsible factor, which was further confirmed by DSC, FTIR studies, and X-RD studies. SEM photographs of batch SD4 revealed porous nature of particle surface. Conclusion: Modified forms of natural carriers prove beneficial in dissolution enhancement of poorly soluble drugs and exhibited a great potential in novel drug delivery systems.
Keywords: Differential scanning colorimetry; glimepiride; modified gum karaya; physical mixture; scanning electron microscopy; solid dispersion; X-ray diffraction